Transcriptional control of a plant stem cell niche - Busch, Wolfgang; Miotk, Andrej; Zhao, Zhong; Forner, Joachim; Daum, Gabor; Suzaki, Takuya; Schuster, Christoph; Schultheiß, Sebastian J.; Leibfried, Andrea; Haubeiß, Silke; Ha, Nati; Chan, Raquel L.; et al. (Developmental cell, 2010)
Summary: Despite the independent evolution of multicellularity in plants and animals, the basic organization of their stem cell niches is remarkably similar. Here, we report the genome-wide regulatory potential of WUSCHEL, the key transcription factor for stem cell maintenance in the shoot apical meristem of the reference plant Arabidopsis thaliana. WUSCHEL acts by directly binding to at least two distinct DNA motifs in more than 100 target promoters and preferentially affects the expression of genes with roles in hormone signaling, metabolism, and development. Striking examples are the direct transcriptional repression of CLAVATA1, which is part of a negative feedback regulation of WUSCHEL, and the immediate regulation of transcriptional repressors of the TOPLESS family, which are involved in auxin signaling. Our results shed light on the complex transcriptional programs required for the maintenance of a dynamic and essential stem cell niche.